ترجمة الثقافة بين العربية والملايوية : دراسة تطبيقية على الفئات الثقافية لحسن غزالة - Rabiatul Adawiyah Md Ali Shifudin (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
The aim of the study is to shed light on the subject of translating culture between the Arabic and the Malay languages based on the eight cultural categories established and developed by Hasan Ghazala who had based it upon the criticism of the five cultural categories presented by Peter Newmark. The eight cultural categories include religious culture, social culture, political culture, mental and emotional culture, linguistic culture, literary culture, ecological as well as the material culture. These categories are more comprehensive and clear, which makes them worth studying and researching. In addition to the nature of the study and its methodology, this study also focused on the most important theories related to the translation of culture, discussing issues in translating culture itself, as well as presenting the most effective methods and strategies to overcome cultural barriers by providing examples and evidences for the translation of concepts and cultural elements between Arabic and Malay. This study is based on three main approaches: the inductive method for the most important studies on cultural translation, the descriptive approach to describe its phenomenon, as well as the analytical approach to explain the cultural categories of Hasan Ghazala. This study concluded that culture can indeed be translated; however, the translator must rely on the best methods and strategies to convey cultural concepts and terms. This entails that there is no specific strategy or procedure that a translator must follow in translating culture; rather, every culture requires a unique approach in translating into the target language.